Question
upstudy study bank question image url

\( 1 \in \) Solve the equation using the quadratic formula. \[ x^{2}-4 x+40=0 \] The solution set is \( \} \). (Simplity your answer. Type an exact answer, using radicals and \( i \) as needed. Use integers or fractions for any numbers in the expression. Use a comma to separate 0 of 1.5 .73 answers as needed.)

Ask by Schmidt Rodriquez. in the United States
Feb 17,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 2 - 6i \) and \( x = 2 + 6i \).

Solution

Solve the equation(The complex numbers system) by following steps: - step0: Solve using the quadratic formula in the complex numbers system: \(x^{2}-4x+40=0\) - step1: Solve using the quadratic formula: \(x=\frac{4\pm \sqrt{\left(-4\right)^{2}-4\times 40}}{2}\) - step2: Simplify the expression: \(x=\frac{4\pm \sqrt{-144}}{2}\) - step3: Simplify the expression: \(x=\frac{4\pm 12i}{2}\) - step4: Separate into possible cases: \(\begin{align}&x=\frac{4+12i}{2}\\&x=\frac{4-12i}{2}\end{align}\) - step5: Simplify the expression: \(\begin{align}&x=2+6i\\&x=\frac{4-12i}{2}\end{align}\) - step6: Simplify the expression: \(\begin{align}&x=2+6i\\&x=2-6i\end{align}\) - step7: Rewrite: \(x_{1}=2-6i,x_{2}=2+6i\) To solve the equation \( x^{2}-4x+40=0 \) using the quadratic formula, we can identify the coefficients: - \( a = 1 \) - \( b = -4 \) - \( c = 40 \) The quadratic formula is given by: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Now, let's calculate the discriminant \( b^2 - 4ac \): \[ b^2 - 4ac = (-4)^2 - 4 \cdot 1 \cdot 40 = 16 - 160 = -144 \] Since the discriminant is negative, we will have complex solutions. Now we can substitute the values into the quadratic formula: \[ x = \frac{-(-4) \pm \sqrt{-144}}{2 \cdot 1} = \frac{4 \pm \sqrt{-144}}{2} \] We know that \( \sqrt{-144} = 12i \), so we can continue: \[ x = \frac{4 \pm 12i}{2} = 2 \pm 6i \] Thus, the solutions are: \[ x_{1} = 2 - 6i, \quad x_{2} = 2 + 6i \] The solution set is: \[ \{ 2 - 6i, 2 + 6i \} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( x^{2} - 4x + 40 = 0 \) using the quadratic formula, we identify \( a = 1 \), \( b = -4 \), and \( c = 40 \). The quadratic formula is given by: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Substituting our values in, we first calculate the discriminant: \[ b^2 - 4ac = (-4)^2 - 4 \cdot 1 \cdot 40 = 16 - 160 = -144 \] Since the discriminant is negative, we will have complex roots. Now plugging into the formula: \[ x = \frac{-(-4) \pm \sqrt{-144}}{2 \cdot 1} = \frac{4 \pm \sqrt{-144}}{2} = \frac{4 \pm 12i}{2} = 2 \pm 6i \] Thus, the solution set is \( \{ 2 + 6i, 2 - 6i \} \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy